JavaScript : best practice. - Kolce, James; Kröger, Moritz; C̆urić, Ivan; Saeed, Samier; Mott, Jeff; Green, M. David; Buckler, Craig (SitePoint, 2018)
There's no doubt that the JavaScript ecosystem changes fast. Not only are new tools and frameworks introduced and developed at a rapid rate, the language itself has undergone big changes with the introduction of ES2015 (aka ES6). Understandably, many articles have been written complaining about how difficult it is to learn modern JavaScript development these days. We're aiming to minimize that confusion with this set of books on modern JavaScript. This book presents modern JavaScript best practice, utilizing the features now available in the language that enable you to write more powerful code that is clean, performant, maintainable, and resusable. It contains: The Anatomy of a Modern JavaScript Application by James Kolce Clean Code with ES6 Default Parameters & Property Shorthands by Moritz Kruger JavaScript Performance Optimization Tips: An Overview by Ivan CuriC JavaScript Design Patterns: The Singleton by Samier Saeed JavaScript Object Creation: Patterns and Best Practices by Jeff Mott Best Practices for Using Modern JavaScript Syntax by M. David Green Flow Control in Modern JS: Callbacks to Promises to Async/Await by Craig Buckler JavaScript's New Private Class Fields, and How to Use Them by Craig Buckler This book is for all front-end developers who wish to improve their JavaScript skills. You'll need to be familiar with HTML and CSS and have a reasonable level of understanding of JavaScript in order to follow the discussion.